2021
DOI: 10.1371/journal.pone.0257658
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in COVID-19 mitigation behaviors: The roles of age, gender, psychological state, and financial status

Abstract: The present study examined individual characteristics potentially associated with changes in mitigation behaviors (social distancing and hygiene) recommended by the Centers for Disease Control and Prevention. Analysis of online survey responses from 361 adults, ages 20–78, with US IP addresses, identified significant correlates of adaptive behavioral changes, with implications for preventive strategies and mental health needs. The extent to which individuals changed their mitigation behaviors was unrelated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 37 publications
8
24
0
Order By: Relevance
“…In a previous study conducted prior to the development of effective vaccines against the COVID-19 (Myerson et al, 2021), we observed that psychological distress appeared to interfere with CDC-recommended mitigation behaviors, particularly those that Frontiers in Psychology 09 frontiersin.org could be thought of as "socially-distancing. " We hypothesized that such behaviors could exacerbate the feelings of social isolation that people might be experiencing, and the more distressed they were, the more likely they were to avoid making things worse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study conducted prior to the development of effective vaccines against the COVID-19 (Myerson et al, 2021), we observed that psychological distress appeared to interfere with CDC-recommended mitigation behaviors, particularly those that Frontiers in Psychology 09 frontiersin.org could be thought of as "socially-distancing. " We hypothesized that such behaviors could exacerbate the feelings of social isolation that people might be experiencing, and the more distressed they were, the more likely they were to avoid making things worse.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the increase in psychological distress associated with the pandemic appears to have been greater in younger adults than in older adults ( Breslau et al, 2021 ), contrary to what one might have expected given the age-related differences in the personal consequences of COVID-19 infection ( Williamson et al, 2020 ; Bosman et al, 2021 ; Lo et al, 2021 ). Appropriately enough, older adults also appear to be more likely to engage in CDC-recommended mitigation behaviors (e.g., social distancing) despite their lower levels of distress ( Masters et al, 2020 ; Myerson et al, 2021 ). The possibility that infection could have more severe consequences for older adults does not appear to explain their mitigation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimates in the older population, who also contributed most to the estimates of waning against severe disease, are likely less affected by bias owing to lower incidence in these age groups, as suggested by serologic data, 28 and better adherence to risk mitigation, as observed in other contexts. 29 30 …”
Section: Discussionmentioning
confidence: 99%
“…Trust in government and partisan self-identification are the independent variables of primary interest. Several control variables that have been found to shape attitudes on COVID-19 mitigation were also included: evangelical identity, partisan self-identification, age, gender, education, and COVID-19 vaccination status ( Adams et al, 2021 ; Corcoran et al, 2021 ; DeMora et al, 2021 ; Myerson et al, 2021 ; Viskupic et al, 2022 ). The survey also included an attention check question, which 98.3% participants answered correctly.…”
Section: Methodsmentioning
confidence: 99%